Introduction: Ambivalence and the social processes of immigrant inclusion. (February 2019) - Boccagni, Paolo; Kivisto, Peter
Ambivalence as an interpretive tool in sociology refers to the social experience of any complex, cognitively confusing, or emotionally charged phenomenon that calls simultaneously for opposite reactions. Migrants' life conditions, as this Special Issue illustrates, are particularly subject to ambivalence. This introduction reviews the predominant understandings of ambivalence as a sociological category, its specific relevance in migration studies, and its implications for empirical research. It then reviews the articles in this Special Issue that are collectively intended to advance our understanding of the relevance of ambivalence for migration studies.